The Role of Behavioral Finance in Student Investment Decision Making: Evidence from University Investment Galleries in Bandung City - Ivan Gumilar Sambas Putra; Yana Hendayana; Dede Hertina (Cita konsultindo, 2026)
This study aims to examine the influence of behavioral finance on investment decision-making among university students participating in Indonesia Stock Exchange investment galleries in Bandung City. The study adopts a behavioral finance perspective by focusing on psychological biases, including overconfidence, loss aversion, herding behavior, and fear of missing out. A quantitative explanatory approach was employed using a survey method to collect data from student investors, which were analyzed using multiple regression techniques. The results show that loss aversion and herding behavior significantly influence students’ investment decisions, indicating that risk avoidance and social influence play a dominant role in shaping investment behavior. Meanwhile, overconfidence and fear of missing out do not have a significant effect on investment decisions in this context. Overall, the findings suggest that student investors’ decisions are strongly affected by behavioral factors rather than purely rational considerations. This study provides empirical evidence on behavioral finance in an academic investment setting and offers practical insights for universities, investment gallery managers, and financial education institutions in designing behavioral-based financial literacy programs to improve the quality of investment decision-making among young investors.